2021
DOI: 10.3389/fonc.2021.715635
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA FOXD3-AS1 Promotes the Malignant Progression of Nasopharyngeal Carcinoma Through Enhancing the Transcription of YBX1 by H3K27Ac Modification

Abstract: BackgroundLong noncoding RNAs (lncRNAs) can affect the progression of various tumors, including nasopharyngeal carcinoma (NPC). Here, lncRNA FOXD3-AS1 is highly expressed in NPC tissues through bioinformatics analysis and related to the malignant progression of NPC.MethodsBioinformatics analysis and real-time reverse transcription quantitative PCR(RT-qPCR) assay were applied to identify the expression of FOXD3-AS1 in NPC tissues and cells. Specific short hairpin RNAs (shRNAs) or overexpression plasmids were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…FOXD3-AS1 has been shown to have predictive value and functional roles in various diseases, including breast cancer, cervical cancer, nasopharyngeal carcinoma, cerebral ischemia/reperfusion injury, cardiomyocyte injury, allergic rhinitis, and so on [ 15 – 17 , 27 , 28 ]. Furthermore, FOXD3-AS1 has been found in nuclear or cytoplasm fractions, and its molecular mechanisms include acting as competing endogenous RNA [ 15 , 29 ], acting as mediators for gene promotor loci and histone modification factor interaction [ 19 ], stimulating proteins expression [ 20 ], interacting and sequestering proteins, and so on [ 14 , 18 ]. In this study, we found that FOXD3-AS1 was upregulated in all primary subtypes of LC at an early stage and increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FOXD3-AS1 has been shown to have predictive value and functional roles in various diseases, including breast cancer, cervical cancer, nasopharyngeal carcinoma, cerebral ischemia/reperfusion injury, cardiomyocyte injury, allergic rhinitis, and so on [ 15 – 17 , 27 , 28 ]. Furthermore, FOXD3-AS1 has been found in nuclear or cytoplasm fractions, and its molecular mechanisms include acting as competing endogenous RNA [ 15 , 29 ], acting as mediators for gene promotor loci and histone modification factor interaction [ 19 ], stimulating proteins expression [ 20 ], interacting and sequestering proteins, and so on [ 14 , 18 ]. In this study, we found that FOXD3-AS1 was upregulated in all primary subtypes of LC at an early stage and increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
“…[15-17, 27, 28]. Furthermore, FOXD3-AS1 has been found in nuclear or cytoplasm fractions, and its molecular mechanisms include acting as competing endogenous RNA [15,29], acting as mediators for gene promotor loci and histone modification factor interaction [19], stimulating proteins expression [20], interacting and sequestering proteins, and so on [14,18]. In this study, we found that FOXD3-AS1 was upregulated in all primary subtypes of LC at an early stage and increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we identified that TBX1 was regulated by NBR2 through H3K27 acetylation (H3K27ac). As one of the most typical histone modifications, H3K27ac was an important epigenetic mechanism involved in the action mode of long noncoding RNA to regulate gene expression. As reported formerly, H3K27ac mediated the regulation of ITGB8 by LINC00472 in renal clear cell carcinoma; DACT1 was regulated by LncRNA CRNDE through H3K27ac in osteoarthritis; FOXD3-AS1 increased the expression of YBX1 by enriching H3K27ac in nasopharyngeal carcinoma . We herein examined whether H3K27ac also mediated the regulation of TBX1 by NBR2 in MWCNTs-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 79%
“…YBX1 is associated with histone modification. H3K27ac is highly enriched in the YBX1 promoter and promotes YBX1 mRNA transcription and protein translation (Yang et al, 2021). YBX1 can also activate p300 and alter histone acetylation landscape to promote chromatin relaxation (Davies et al, 2014).…”
Section: Discussionmentioning
confidence: 99%